Collaboration of the Joint Research Centre and European Customs Laboratories for the Identification of New Psychoactive Substances - Guillou, Claude; Reniero, Fabiano; Lobo Vicente, Joana; Holland, Margaret; Kolar, Kamil; Chassaigne, Hubert; Tirendi, Salvatore; Schepers, Herve (Current pharmaceutical biotechnology, 2018)
The emergence of psychoactive designer drugs has significantly increased over the last few years. Customs officials are responsible for the control of products entering the European Union (EU) market. This control applies to chemicals in general, pharmaceutical products and medicines. Numerous products imported from non-EU countries, often declared as 'bath salts' or 'fertilizers', contain new psychoactive substance (NPS). These are not necessarily controlled under international law, but may be subject to monitoring in agreement with EU legislation. This situation imposes substantial challenges, for example, for the maintenance of spectral libraries used for their detection by designated laboratories. The chemical identification of new substances, with the use of powerful instrumentation, and the time needed for detailed analysis and interpretation of the results, demands considerable commitment. The EU Joint Research Centre endeavors to provide scientific support to EU Customs laboratories to facilitate rapid identification and characterisation of seized samples. In addition to analysing known NPS, several new chemical entities have also been identified. Frequently, these belong to NPS classes already notified to the European Monitoring Centre for Drugs and Drug Addiction (EMCDDA) by the European Early- Warning System (EWS). The aim of this paper is to discuss the implementation of workflow mechanisms that are in place in order to facilitate the monitoring, communication and management of analytical data. The rapid dissemination of this information between control authorities strives to help protect EU citizens against the health risks posed by harmful substances.